Os significados das práticas de trabalho construídos pelos profissionais de saúde que assistem pacientes com HIV/AIDS - Greggio, Eloisa Vilas Boas Rosas (2006)
The present study was developed with a professional team that works with HIV/Aids patients in a public hospital of Fortaleza. It aimed to identify, comprehend and analyze the meanings these health professionals give to their practice at this main reference public hospital for infectious- contagious diseases. Qualitative approach was applied, the data research being collected through interviews and focal group based on psychodramatic theory. Ten professionals from Specialized Assistance Service – SAE, also known, at the hospital, by ambulatory, were interviewed to identify their technical core competences; know the nature of human relations at work; study their links to the institution; research how these professionals are seen by society as well as the difficulties and/or facilities in what concerns their professional practice; investigate the links between strategic management vision and crew practices. The interview contents was analyzed based upon the Bardin´s (2004) methodological principles, which commend a treatment of the information of the messages that can be made through a analysis of the meanings (thematic) or a analysis of the significance (lexical, of proceedings). It was noticed a heterogenic perception in the community of these professionals on their necessary knowledge, abilities and attitudes to the efficient work, and how these professionals experiment different and contradictory feelings in consequence of their practices and believe that society have stereotypes about them. Based upon the results of theses analyzes it was suggested the planning of a local team work development with the different kinds of professionals that lead with these patients, once it was noticed a necessity of interprofessional attitudes and practices; the implementation of human research administration by competences and a possible change in the way of administration of this specialized work in linking it with the strategic management of human researches and the proceeding of psychological and managerial nature with the health team from the HSJ SAE, once it was identified the necessity of this kind of intervention in this professional group.